Studi Kasus Kontrol : Riwayat Obstetri Buruk dan Riwayat Peristiwa Kehidupan Negatif dengan Riwayat Depresi Antenatal - Hasanah, Zumroh; Novembriani, Rizqie Putri (ARTERI : Jurnal Ilmu Kesehatan, 2024)
Antenatal depression has a significant impact on the well-being of both mothers and children. It can lead to adverse outcomes such as spontaneous miscarriage, hypertensive disorders, antepartum hemorrhage, impaired fetal growth, preterm birth, low birth weight, low APGAR scores, intensive newborn care, and postpartum and parental depression, linked to risky behaviors like substance abuse (e.g., alcoholism and smoking), reduced utilization of healthcare services, poor appetite, and thoughts of self-harm. The aim of this study was to analyze the correlation between poor obstetric history, negative life events, and the risk of antenatal depression. This research employed a case-control study design and involved 58 pregnant women (29 case, 29 control) attending antenatal check-ups at the Jagir and Tanah Kali Kedinding health centers in Surabaya, who met the inclusion criteria. Poor obstetric history and negative life events were considered as independent variables and were assessed using a general questionnaire. The Edinburgh Postnatal Depression Scale (EPDS) with a cutoff value of 10 was used to determine the dependent variable, which was antenatal depression. However, the statistical analysis indicated that neither poor obstetric history nor negative life events significantly affected the risk of antenatal depression, with p-values of 0.092 and 0.142 respectively. The study suggests the need for further research with larger samples and different research designs to better understand the risk factors for antenatal depression. Moreover, it is recommended that maternal healthcare facilities routinely and periodically implement antenatal depression screening.